Risk Factors for Ischemic Heart Disease among Patients Admitted to Coronary Care Unit (CCU) in AL-Hussain Hospital in Karballa (Iraqi Journal of Medical Sciences, 2016)
Background:Adequate control of cardiovascular disease risk factors and health habits are important for preventing ischemic heart disease, but it has been reported that many patients remain uncontrolled despite regular care.Objective:To identify some of the risk factors of ischemic heart diseases among patients admitted to coronary care unit (CCU).Methods: A hospital based case-control study was conducted in AL-Hussain Hospital in Karballa, from January 2007 to October 2007. The study included 300 cases of ischemic heart disease admitted to coronary care unit (CCU) of the hospital during the study period, and 300 age & sex matched controls, who attended the outpatient clinic of the same hospital. All the participants were interviewed with a special questionnaire form. In addition the weight and height were measured for both cases and controls to determine their body mass index (BMI).Result:73 (24.3%) of the cases were in the age group (60-69) years. The females accounts for two third of cases, 199 (66.3%) in comparison to males 101 (33.7%).The study showed a statistical significant association between the following risk factors and admission to CCU: smoking, alcohol consumption, obesity, hypertension, diabetes, and positive family history of various cardiovascular diseases among first degree relatives of the cases.Conclusions:The admission to CCU was more common in the age group (60-69) years and the females were more likely than males need for CCU admission, patients with the following risk factors were in more need to CCU admission than others: smoking, elevated body mass index (BMI), hypertension, diabetes and positive family history of various cardiovascular diseases among first degree relatives of the cases.Key words:risk factors, CCU admission
Keywords: risk factors; CCU admission